Basic features of Ne*–HX (X = Cl, Br) chemi-ionization reactions. Issue 12 (8th March 2022) - Falcinelli, Stefano; Vecchiocattivi, Franco; Brunetti, Brunetto Giovanni; Parriani, Marco; Gigliotti, Giovanni; Stranges, Stefano; Pirani, Fernando
Abstract : Ionization cross sections for Ne*( 3 P2, 0 )–HX (X = Cl, Br) chemi-ionizations are presented in the 0.02–0.5 eV collision energy range. Abstract : Total and partial ionization cross sections for Ne*( 3 P2, 0 )–HX (X = Cl, Br) are presented in a comparative way as a function of the collision energy between 0.02–0.5 eV. New mass spectrometric data on Ne*–HBr chemi-ionization are discussed and analyzed with already published data on Ne*–HCl, highlighting similarities and differences of the collisional stereodynamics of the two systems. Basic features of the interaction potentials, driving reactive collisions, suggest that reaction channels, leading to the formation of parent HX + ions in the ground and excited electronic state and to the formation of associated NeHX + ions as well as of NeH + proton transfer species, are selectively opened within angular cones exhibiting different orientation and acceptance.